The association between perfectionism and academic procrastination among undergraduate nursing students: The role of self‐efficacy and resilience - Haitao Huang; Yueming Ding; Yipei Liang; Xiao Wan; Qianwen Peng; Yiming Zhang; Deren Kong; Chaoran Chen (Wiley, 2023)
Abstract Aims This study aimed to investigate the associations between perfectionism and undergraduate nursing students' academic procrastination, the mediating effects of self‐efficacy and the moderating role of resilience. Design A cross‐sectional survey. Methods The survey was conducted from March to May 2022 with a sample of 587 undergraduate nursing students in two undergraduate universities in China. A descriptive statistical approach, Pearson's correlation analysis and the Hayes' PROCESS Macro model 4 and 14 were used to analyse the available data. Results Adaptive perfectionism and maladaptive perfectionism negatively and positively predicted academic procrastination in nursing undergraduates, respectively. Self‐efficacy played a partially mediating role in the association between adaptive perfectionism and academic procrastination. Furthermore, resilience played a moderating role in the association between adaptive perfectionism and academic procrastination. Conclusions Maladaptive perfectionism and low levels of resilience and self‐efficacy may increase the risk of academic procrastination among nursing undergraduates. Nursing educators can take measures to decrease the risk of academic procrastination among nursing undergraduate students by guiding them to cultivate adaptive perfectionism tendencies and improve their self‐efficacy and resilience. Impact The findings of this study can be used to develop targeted coping and prevention measures for nursing educators to reduce the incidence of academic procrastination among nursing undergraduates. Patient or Public Contribution Five hundred eighty‐seven undergraduate nursing students from two undergraduate universities participated in the study and responded to questions on perfectionism and academic procrastination, etc.